Global Existence of Solutions of the Navier-Stokes-Maxwell System in Besov Spaces (Journal of Mathematical Study, 2019)
The motion of hydro-magnetic fluid can be described by Navier-Stokes-Maxwell system. In this paper, we prove global existence and uniqueness for the solutions of Navier-Stokes-Maxwell system in 3 dimensional space for small data.